Pelestarian patriotisme di sekolah rendah oleh siswa guru sejarah Institut Pendidikan Guru Malaysia - Muhamad Azian, Saad (2021)
Malaysia is struggling to sustain the value of patriotism in schools. The polemic in sustaining the value of patriotism among students is seen through changes in government policies related to the teaching of history. This study investigated the understanding of patriotism and the practices of its value among the trainee teachers of history as a subject in the Institute of Teacher Education (IPG) and examined the relationship between the understanding and the practice of the value of patriotism as well as the way they inculcate the value among primary school pupils. The research population comprised of 444 trainee teachers of history in the Bachelor of Teaching (PISMP) Program in 27 IPGs and the research sample involved 276 trainee teachers in 13 IPGs. The study used the mixed methodology design. Questionnaires were used to collect quantitative data while interviews, observations and document study were used for obtaining qualitative data. The understanding of the value of patriotism was at a high level (min 4.06) and the practice of the value of patriotism among the trainee teachers of history was also at a high level (min 4.48). There was a significant relationship between the understanding of the value of patriotism and the practice of the value of patriotism among the trainee teachers of history (r 0.434). The inculcation of the value of patriotism in the classroom occurred as planned in the Daily Lesson Plan (RPH), though it was less emphasized by the trainee teachers of History because it depended on the element of citizenship and the value of civics (K) in the Standard of Learning (SP). At the IPG level, patriotism is seen as a hidden curriculum that is taught implicitly to trainee teachers. The study suggests the need for a standardized mechanism for the inculcation of patriotism values, effective mentoring courses, a revised instrument of the values of patriotism for practicum assessment, diversified lessons and the adoption of the 21st-Century Pedagogy in the teaching and learning of history. Sustaining values of patriotism at the primary school level is expected to be an important agenda for history teachers in t teaching history.